Implementasi blockchain dalam keamanan data medis: tinjauan sistematis publish or perish - Rusdha, Salma Nasira; Fauzan Ali Rahman; Zelly Salmiyati Rahman Zam; Vidi Prima Mizan; Fathihanna Yusuf; Oktarina, Rahmi (Computer Science and Information Technology, 2026)
The digitalization of healthcare services offers substantial opportunities to improve efficiency and quality of care; however, it also introduces significant challenges related to the security, privacy, and integrity of medical data. The literature indicates that conventional Electronic Health Record (EHR) systems remain vulnerable to data breaches, information manipulation, and system failures due to their centralized architecture. This review examines the development of blockchain technology as a potential solution for modern healthcare data management. The study employs a systematic literature review using the Publish or Perish approach, with Google Scholar as the data source to identify relevant scientific articles, which were subsequently screened based on predefined inclusion and exclusion criteria and analyzed qualitatively. Owing to its characteristics of decentralization, immutability, strong cryptography, and the use of smart contracts for access control, blockchain offers significant improvements in medical data security, transparency, and interoperability. Its applications have been reported in EHR systems, telemedicine, pharmaceutical supply chains, medical imaging, and clinical trial data management. Nevertheless, several limitations continue to hinder widespread adoption, including scalability issues, computational overhead, integration complexity with legacy systems, the transparency–privacy trade-off, and regulatory challenges such as compliance with data protection laws and international standards. Future research trends point toward the integration of blockchain with artificial intelligence, the Internet of Medical Things (IoMT), and federated learning, as well as the development of lightweight blockchain solutions for resource-constrained environments. Overall, blockchain demonstrates considerable potential to strengthen the security and reliability of healthcare information systems; however, its implementation requires a gradual, standardized, and regulation-compliant approach.